Ecological Factors in Changing Economy and Social Organization Among the Rupert House Cree - Knight, Rolf (Anthropology Papers / National Museum of Canada, 1968)
A brief ethnographic study done for the National Museum of Canada in 1961-62 focusing on the then continuing economic importance of hunting and trapping for the native people of the region. --Author's description